Corruptionary natatanging diksyonaryo ng mga salitang korapsyon. - Center for People Empowerment in Governance (Lungsod ng Quezon CenPEG Books, 2008)
Tagalog dictionary of corrupt and political terms.
In Tagalog.
Keywords: Corruption -- Dictionaries -- Tagalog; Political corruption -- Philippines -- Dictionaries -- Filipino